Answer:
Maggie spent =30
Karen spent = 10
Jasmine spent =20
Step-by-step explanation:
In this we use algebra to solve.we give the sisters unknowns, to help us solve the equation.
we dont know how much jasmine used so we give her the unknown x.you can use any letter but ill us x.
karen used half as much as karen so we give her 1/2x because it was half of jasmine.maggie used 3 times that of karen so w give her 3(1/2x).
maggie =3(1/2x)
Karen =1/2x
jasmine =x
3(1/2x) + 1/2x + x = 60
3/2x + 1/2x + x = 60
2x + x = 60
3x=60
x=20
where we have x =we replace with 20
e.g karen 1/2x => 1/2 x 20 =10
if you need any clarifications please do tell me in the comment section.i would like to help more if you need help.thx
Hope this helps and if it does mark as branliest anwer thx
Answer:
<h3>f =27</h3>
Step-by-step explanation:
![12 = f - 13-2](https://tex.z-dn.net/?f=12%20%3D%20f%20-%2013-2)
Collect like terms and simplify
![12+13+2 = f\\27 =f](https://tex.z-dn.net/?f=12%2B13%2B2%20%3D%20f%5C%5C27%20%3Df)
Switch sides
![f = 27](https://tex.z-dn.net/?f=f%20%3D%2027)
V=L X W X H
1,296=6 x w x 24
1,296=144 x w
1296/144=w
9=width
To factor both numerator and denominator in this rational expression we are going to substitute
![n^{2}](https://tex.z-dn.net/?f=n%5E%7B2%7D%20)
with
![x](https://tex.z-dn.net/?f=%20x%20)
; so
![n^{2} =x](https://tex.z-dn.net/?f=n%5E%7B2%7D%20%3Dx)
and
![n ^{4} = x^{2}](https://tex.z-dn.net/?f=n%20%5E%7B4%7D%20%3D%20%20x%5E%7B2%7D%20%20)
. This way we can rewrite the expression as follows:
![\frac{n^{4}-11n^{2} +30 }{n^{2}-7n^{2} +10 } = \frac{ x^{2} -11x+30}{ x^{2} -7x+10}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bn%5E%7B4%7D-11n%5E%7B2%7D%20%2B30%20%7D%7Bn%5E%7B2%7D-7n%5E%7B2%7D%20%2B10%20%7D%20%3D%20%20%5Cfrac%7B%20x%5E%7B2%7D%20-11x%2B30%7D%7B%20x%5E%7B2%7D%20-7x%2B10%7D%20)
Now we have two much easier to factor expressions of the form
![a x^{2} +bx+c](https://tex.z-dn.net/?f=a%20x%5E%7B2%7D%20%2Bbx%2Bc)
. For the numerator we need to find two numbers whose product is
![c](https://tex.z-dn.net/?f=c)
(30) and its sum
![b](https://tex.z-dn.net/?f=b)
(-11); those numbers are -5 and -6.
![(-5)(-6)=30](https://tex.z-dn.net/?f=%28-5%29%28-6%29%3D30)
and
![-5-6=-11](https://tex.z-dn.net/?f=-5-6%3D-11)
.
Similarly, for the denominator those numbers are -2 and -5.
![(-2)(-5)=10](https://tex.z-dn.net/?f=%28-2%29%28-5%29%3D10)
and
![-2-5=-7](https://tex.z-dn.net/?f=-2-5%3D-7)
. Now we can factor both numerator and denominator:
![\frac{ x^{2} -11x+30}{ x^{2} -7x+10} = \frac{(x-6)(x-5)}{(x-2)(x-5)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20x%5E%7B2%7D%20-11x%2B30%7D%7B%20x%5E%7B2%7D%20-7x%2B10%7D%20%3D%20%5Cfrac%7B%28x-6%29%28x-5%29%7D%7B%28x-2%29%28x-5%29%7D%20)
Notice that we have
![(x-5)](https://tex.z-dn.net/?f=%28x-5%29)
in both numerator and denominator, so we can cancel those out:
![\frac{x-6}{x-2}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx-6%7D%7Bx-2%7D%20)
But remember than
![x= n^{2}](https://tex.z-dn.net/?f=x%3D%20n%5E%7B2%7D%20)
, so lets replace that to get back to our original variable:
![\frac{n^{2}-6 }{n^{2}-2 }](https://tex.z-dn.net/?f=%20%5Cfrac%7Bn%5E%7B2%7D-6%20%7D%7Bn%5E%7B2%7D-2%20%7D%20)
Last but not least, the denominator of rational expression can't be zero, so the only restriction in the variable is
![n^{2} -2 \neq 0](https://tex.z-dn.net/?f=n%5E%7B2%7D%20-2%20%5Cneq%200)
![n^{2} \neq 2](https://tex.z-dn.net/?f=%20n%5E%7B2%7D%20%20%5Cneq%202)